UCI sports nutrition project: Does cycling create a "perfect storm" for bone health? Cycling-specific challenges to bone and nutritional strategies to overcome these - Saffioti, N.; Takarabe, L. L.; Perfeito, L. A. M.; Ribeiro, W. J. D.; Hilkens, L.; Van Dijk, J.; Dolan, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
As a group, cyclists tend to have lower bone mass compared with other athletes, and nonathlete controls which may have negative consequences for fracture risk and longer term bone health. There are several cycling-specific factors that may contribute to this finding. These include, the low-impact, repetitive load nature of cycling which provides limited stimulus for bone metabolism; metabolic perturbations that occur following prolonged cycling that may lead to a transient increase in the rate of bone resorption; and nutritional factors, including low energy availability or nutrient inadequacy. Furthermore, many endurance cyclists are naturally lean and light, which may result from both genetic predisposition and long-term training adaptations. In turn, they may also have lower bone mass. None of these factors stand out as the primary cause of the low bone mass reported in cyclists but, instead, may combine to create a "perfect storm" to challenge cyclist bone health. Given these multiple potential challenges to bone health, a multifaceted approach may be required to combat them. On an individual level, nutritional strategies, including ensuring adequate energy, carbohydrate, protein, calcium, vitamin D, and other important micronutrients may be key to protecting cyclist bone health. Integrating brief bouts of high-impact loading within the training regimen and ensuring adequate sleep and recovery are also recommended. The onus should not remain solely on the individual, however, and cycling teams and organizational bodies have a key role to play in providing screening and educational strategies to support cyclists bone health.